Criminal Law Enforcement of Book Copyright Infringement in Digital Market Places in The Ecosystem E-Commerce Through Restorative Justice - Putra, Mohamad Rizki Agung (Ius Poenale, 2023)
The enforcement of criminal law against book copyright infringement in Indonesia is inadequate, lacking legal certainty and failing to provide restorative justice for copyright holders due to outdated regulations. This study, using a normative juridical approach with descriptive analysis and empirical comparison, reveals that such enforcement is categorized as a 'complaint offense,' starting with the reception of complaints and proceeding to mediation, followed by judicial processes if mediation fails. It also highlights that copyright protection involves automatic regulatory mechanisms, a registration system for exclusive, moral, and economic rights, and combines proactive educational outreach with repressive marketplace monitoring and customs collaborations. Furthermore, the research explores Restorative Justice, focusing on mediation and arbitration in commercial courts for fair restitution, aiming to compensate materially and morally. The findings suggest expanding restitution concepts in Restorative Justice to align with global copyright norms and the growth of E-Commerce, thereby enhancing protection for copyright holders in the digital era.